2014
DOI: 10.1371/journal.pone.0096664
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Metabolism Is Significantly Altered in the Liver Tumor Tissue of Hepatocellular Carcinoma Patient

Abstract: BackgroundSorafenib, the drug used as first line treatment for hepatocellular carcinoma (HCC), is metabolized by cytochrome P450 (CYP) 3A4-mediated oxidation and uridine diphosphate glucuronosyl transferase (UGT) 1A9-mediated glucuronidation. Liver diseases are associated with reduced CYP and UGT activities, which can considerably affect drug metabolism, leading to drug toxicity. Thus, understanding the metabolism of therapeutic compounds in patients with liver diseases is necessary. However, the metabolism ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…The biologic impact of locally reduced glucuronidation capacity in diseased tissues remains to be examined but could be of clinical relevance to susceptibility to kidney cancer or treatment of kidney cancer. The important loss of UGT1A9-and UGT2B7-conjugating activity in tumor kidneys is in line with the reduced expression of several UGT1A and UGT2B7 observed at both mRNA and protein levels in hepatocellular carcinomas (Strassburg et al, 1997;Yan et al, 2014;Ye et al, 2014), UGT1A10 and UGT2B7 in breast cancer Fig. 6.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The biologic impact of locally reduced glucuronidation capacity in diseased tissues remains to be examined but could be of clinical relevance to susceptibility to kidney cancer or treatment of kidney cancer. The important loss of UGT1A9-and UGT2B7-conjugating activity in tumor kidneys is in line with the reduced expression of several UGT1A and UGT2B7 observed at both mRNA and protein levels in hepatocellular carcinomas (Strassburg et al, 1997;Yan et al, 2014;Ye et al, 2014), UGT1A10 and UGT2B7 in breast cancer Fig. 6.…”
supporting
confidence: 54%
“…The decreased glucuronidation activity of kidney tumors relative to normal tissues is of particular relevance in advanced renal clear cell carcinoma treatment strategies, given that sorafenib is an important renal carcinoma anticancer agent (Escudier et al, 2007;Zustovich et al, 2011). It is primarily metabolized by CYP3A4 and UGT1A9 in the liver, but its renal metabolism has not been assessed (Keating and Santoro, 2009;Ye et al, 2014). The biologic impact of locally reduced glucuronidation capacity in diseased tissues remains to be examined but could be of clinical relevance to susceptibility to kidney cancer or treatment of kidney cancer.…”
mentioning
confidence: 99%
“…Sorafenib is metabolized by CYP3A4 (10). In the present study, the expression levels of CYP3A4 were observed to increase during sphere formation.…”
Section: Discussionsupporting
confidence: 55%
“…Sorafenib is a multikinase inhibitor with a high antitumor efficacy that suppresses cell proliferation and induces apoptosis in HCC cell lines (5)(6)(7). A limitation of this approach is that HCC cells acquire resistance to sorafenib (8,9), as it is metabolized by cytochrome P450 (CYP3A4) (10). This has necessitated the development of alternative therapies for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib is also metabolized by CYP3A4-mediated oxidation and UGT1A9-mediated glucuronidation. Ye et al (8) reported that sorafenib metabolism was significantly altered in the liver tumor tissue of a hepatocellular carcinoma patient, due to an evident decrease of the expression level of CYP3A4 and UGT1A9. Boudou-Rouquette et al (9) reported that the UGT1A9 polymorphism (rs17868320) was WBC, white blood cell; RBC, red blood cell; PLT, platelet; AST, aspartate aminotransferase; ALT, alanine aminotransferase; LDH, lactate dehydrogenase; ALP, alkaline phosphatase; γ-GTP, γ-glutamyl transpeptidase; BUN, blood urea nitrogen; HPT, heparin protamine titration; PT, prothrombin time; PTINR, prothrombin time/international normalized ratio; APTT, activated partial thromboplastin time; ATIII, antithrombin III; FDP, fibrin degradation products.…”
Section: Discussionmentioning
confidence: 99%